Physical description and productivity of Landim goats and sheep in Mozambique - Rocha, A.; McKinnon, D.; Wilson, R.T. (1991)
Provides the first full physical description of the Landim goats and sheep of Mozambique; presents and compares the productivity of the two species under the same environmental and management conditions as least squares means; with particular reference to age at first parturition, litter size, reproductive performance, parturition interval, weights at birth and mortality; and discusses the results in relation to the possible role of these types of small ruminants in improving animal productivity in Africa.